Characteristicks: of men, manners, opinions, times ... - Shaftesbury, Anthony Ashley Cooper of ((The Eighteenth Century ; reel 6991, no.01)., 1733)
v. 1. A letter concerning enthusiasm. Sensus communis; an essay on the freedom of wit and humour. Soliloquy, or advice to an author. -- v. 2. An inquiry concerning virtue and merit. The moralists; a philosophical rhapsody. -- v. 3. Miscellaneous reflections on the preceding treatises, & other critical subjects. A notion of the tablature, or judgment of Hercules.